Pariwisata Syariah: Suatu Konsep Kepercayaan dan Nilai Budaya Lokal di Daerah Pedalaman Pilubang, Payakumbuh, Sumatera Barat - Masful, Mila Falma (Jurnal The Messenger, 2017)
West Sumatera have the most visitors on the big day such as Ied Fitr, Christmas and New Year who would come to area attractions such as Padang Beach, Pulau Pasumpahan that also rise sharply. Some of the famous tourist attractions are the Harau Valley and Pemandian Batang Tabik. But lately, about 5 years, Pilubang village, a small village in Payakumbuh offers something different and interesting to the tourists, the sharia travelling. This concept is believed to emerge as Islamic values and local wisdom are mixed into a tourist destination that will demand a lot of circles. By not losing the essence of this area as a village which is very un-Islamic and habitual but actually makes the sale value and attractiveness in the field of travel. Pilubang Resort itself offers a beautiful natural scenery and exotic, local people were friendly, as well as sites with custom rules included therein.